Study Respon Investor Terhadap Opini Going Concern - Aji Prasetyo (Institut Ilmu Sosial dan Manajemen STIAMI, 2017)
This research aims to analyze the response of investors to the going concern opinion on issuers listed on the Indonesia Stock Exchange.The population used in this research are all companies listed on the Indonesia Stock Exchange (IDX) in 2012-2013 so that the number of samples (n) = 106. Determination of sample do with purposive sampling method, samples are selected using criteria specified.Samples of data are collected using literature study and documentation. The data collected will be analyzed with descriptive statistical analysis, Different test and classical assumption. Descriptive statistical analysis was conducted to determine the dispersion and distribution of data. Different test is used to test the differences between the two variables are then used to test the research hypotheses. While the classical assumption test was conducted to test the feasibility of multiple linear regression models were then used to test the research hypotheses.In this research found evidence that there is no difference between the abnormal returns before going concern opinion issued by after receiving going concern opinion, there is no difference between the abnormal return issuers obtain going concern opinion with which to obtain an unqualified opinion and no significant influence going concern opinion to the cumulative abnormal return.